Exfoliation Joint and Its Origins - Kanjanapayont, Pitsanupong (Bulletin of Earth Sciences of Thailand, 2021)
Exfoliation joint is generally used in various terms such as sheet joint or sheet structure. The topography of it is domical hills or bornhardts which is in a dome shape. The origins of exfoliation joint are commonly explained by four theories; pressure release, thermoelastic strain, chemical weathering, compressive stress and extensional fracture. Pressure release theory has many inconsistencies with field and observations, while thermoelastic strain and chemical weathering can not explain for the large scale or deep exfoliation joint. The compressive stress and extensional fracture seems to be the most suitable theory to explain the origin of exfoliation joint.